Analisa Kebutuhan Parkir Pusat Perbelanjaan (Study Kasus Parkir Mega Mall Kota Bengkulu) - Edito Dwi Antoro (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2019)
Abstract As the volume of vehicles increases every year, the need for a parking space is a primary need that must be well prepared by a data center, this aims to minimize the number of congestion and the need for parking space. Mega mall Bengkulu is one of the centers in Bengkulu Province which every day experiences problems of lack of parking space and congestion. The data test method is by means of a field survey by taking the Average Daily Traffic (LHR) at the peak time of vehicles entering and exiting the parking area and measuring the conditions of the parking area / parking area. The data obtained are: parking area capacity, parking volume and demand. parking space. Based on the results of the survey and analysis of parking volume data at Mega Mall Bengkulu which was carried out on September 7 - 9, 2018, it can be concluded that the need for parking space (KRP) for vehicles at Mega Mall Bengkulu details: accommodating cars of 150 SRP on Sunday 9 September 2018 tamping capacity is 150 SRP and the maximum accumulation of motor vehicles is 382 SRP on Sunday, September 9 2018. Capacity is 400 SRP. For the maximum daily parking volume, the vehicle parking area at Mega Mall Bengkulu occurs on Sunday, September 9 2018 with the volume of vehicles 756 and motorcycles in 1911.